THE MEANING OF BEING CANADIAN: A COMPARISON BETWEEN YOUTH OF IMMIGRANT AND NON‐IMMIGRANT ORIGINS - Lee, Jennifer; Hébert, Yvonne (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
The meanings attached to national identity are the most salient citizenship issue today. We analyzed over 300 written responses of Canadian high school youth, of immigrant and non‐immigrant origins, to the question of “What does it mean for me to be/become a Canadian?” The participants related a greater sense of national identity than of ethnic and/or supranational belonging. Youth of immigrant origins used a discourse of becoming and understand multiculturalism to recognize ethnic identities associated with Charter rights. The findings are contextualized in social unrest in other countries, a global migration pattern, and new forms of economic, social, and political domination. Keywords: Canadian identity, immigrant youth, ethnic identity, changing economic conditions Les divers sens donnés à la notion d’identité nationale, telle est la question la plus importante de l’heure en matière de citoyenneté. Les auteures ont analysé plus de 300 réponses écrites de jeunes Canadiens au secondaire, immigrants et non‐immigrants, à la question : « Que veut dire être ou devenir Canadien pour moi ? ». Les participants font état d’un plus grand sentiment d’appartenance au pays qu’à des groupes ethniques ou supranationaux. Les jeunes immigrés adoptent un discours axé sur le devenir et considèrent le multiculturalisme comme la reconnaissance des identités ethniques dans le cadre de la Charte canadienne des droits et libertés. Les résultats de l’étude sont mis en contexte : agitation sociale dans d’autres pays, mouvements migratoires à l’échelle mondiale et nouvelles formes de domination politique, sociale et économique. Mots clés : identité canadienne, jeunes immigrants, identité ethnique, évolution des conditions économiques.